2011
DOI: 10.1021/ja2058617
|View full text |Cite
|
Sign up to set email alerts
|

Shape- and Size-Controlled Synthesis in Hard Templates: Sophisticated Chemical Reduction for Mesoporous Monocrystalline Platinum Nanoparticles

Abstract: Here we report a novel hard-templating strategy for the synthesis of mesoporous monocrystalline Pt nanoparticles (NPs) with uniform shapes and sizes. Mesoporous Pt NPs were successfully prepared through controlled chemical reduction using ascorbic acid by employing 3D bicontinuous mesoporous silica (KIT-6) and 2D mesoporous silica (SBA-15) as a hard template. The particle size could be controlled by changing the reduction time. Interestingly, the Pt replicas prepared from KIT-6 showed polyhedral morphology. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
263
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 386 publications
(270 citation statements)
references
References 41 publications
7
263
0
Order By: Relevance
“…310 Pt single crystals with monodispersed polyhedral and olive-shaped morphologies were synthesized by using KIT-6 (double gyroid structure, Ia 3d) and SBA-15 (2D hexagonal structure, p6mm) mesoporous silica, respectively (Figures 21b and 21c). 311 It is found that the reduction and growth kinetics play a critical role in the rational design of mesoporous crystals. Using mild reducing agents, like ascorbic acid, provides enough time for the reductants to access the inner regions of the mesoporous silica.…”
Section: Mesoporous Templatesmentioning
confidence: 99%
“…310 Pt single crystals with monodispersed polyhedral and olive-shaped morphologies were synthesized by using KIT-6 (double gyroid structure, Ia 3d) and SBA-15 (2D hexagonal structure, p6mm) mesoporous silica, respectively (Figures 21b and 21c). 311 It is found that the reduction and growth kinetics play a critical role in the rational design of mesoporous crystals. Using mild reducing agents, like ascorbic acid, provides enough time for the reductants to access the inner regions of the mesoporous silica.…”
Section: Mesoporous Templatesmentioning
confidence: 99%
“…31 For the fabricated nanoporous gyroid Pt, the electronic continuity was probed using cyclic voltammetry. Cyclic Figure 5a shows the electrocatalytic properties of the nanoporous gyroid Pt compared with commercially available Pt nanoparticle catalysts, including PtB and Pt/C.…”
Section: Electrochemical Properties Of Nanoporous Ptmentioning
confidence: 99%
“…Recently, Yang et al 25 used presynthesized Pt-based 3D nanoparticles to create highly active 3D nanoframes under a spontaneous evolution process in oleylamine ligands. Another straightforward route for the fabrication of nanoporous Pt is to deposit the desired Pt-base materials into templates with defined nanochannels through templated syntheses using mesoporous silica (MCM materials) [29][30][31] or polycarbonate as templates. 32,33 Over recent decades, block copolymers (BCPs) have been extensively investigated because of their ability to self-assemble into one-, two-or 3D periodic nanostructures, according to their compositions and molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to prevent sintering and have an easy recovery of the catalyst from the reaction medium, supports are employed. Carbon, titania, metal-organic frameworks, graphene, mesoporous silica, or various polymers have been successfully applied as supports by several research groups [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%